Ex-situ biogas upgrading in thermophilic trickle bed reactors packed with micro-porous packing materials. (June 2022) - Ghofrani-Isfahani, Parisa; Tsapekos, Panagiotis; Peprah, Maria; Kougias, Panagiotis; Zervas, Athanasios; Zhu, Xinyu; Yang, Ziyi; Jacobsen, Carsten S.; Angelidaki, Irini
Abstract: Two thermophilic trickle bed reactors (TBRs) were packed with different packing densities with polyurethane foam (PUF) and their performance under different retention times were evaluated during ex-situ biogas upgrading process. The results showed that the TBR more tightly packed i.e. containing more layers of PUF achieved higher H2 utilization efficiency (>99%) and thus, higher methane content (>95%) in the output gas. The tightly packed micro-porous PUF enhanced biofilm immobilization, gas-liquid mass transfer and biomethanation efficiency. Moreover, applying a continuous high-rate nutrient trickling could lead to liquid overflow resulting in formation of non-homogenous biofilm and severe deduction of biomethanation efficiency. High-throughput 16S rRNA gene sequencing revealed that the liquid media were predominated by hydrogenotrophic methanogens. Moreover, members of Peptococcaceae family and uncultured members of Clostridia class were identified as the most abundant species in the biofilm. The proliferation of hydrogenotrophic methanogens together with syntrophic bacteria showed that H2 addition resulted in altering the microbial community in biogas upgrading process. Graphical abstract: Image 1 Highlights: Biological biogas upgrading process was evaluated in trickle bed reactors (TBRs). Polyurethane foam (PUF) with different densities were packed inside the TBRs. Dense PUF substantially enhanced biofilm immobilization and H2 mass transfer rate. Biofilm was predominated by syntrophic acetate oxidizing bacteria.